2020
DOI: 10.5194/gmd-13-5583-2020
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of increasing resolution in global and regional climate simulations for European climate extremes

Abstract: Abstract. Many climate extremes, including heatwaves and heavy precipitation events, are projected to worsen under climate change, with important impacts for society. Future projections required for adaptation are often based on climate model simulations. Given finite resources, trade-offs must be made concerning model resolution, ensemble size, and level of model complexity. Here we focus on the resolution component. A given resolution can be achieved over a region using either global climate models (GCMs) or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 81 publications
5
36
0
Order By: Relevance
“…On one hand, the NSWM responses to the nonlinear interaction effects between orography and other forcings tend to be largest in the Pacific-North American sector, which is beyond the scope of this paper, in agreement with Held et al (2002). On the other hand, Iles et al (2019) suggest that increasing the resolution of the orography and coastlines in climate simulations have limited benefits for temperature extremes over Europe, except in reducing hot biases over mountainous regions.…”
Section: Nonlinear Interactionssupporting
confidence: 72%
“…On one hand, the NSWM responses to the nonlinear interaction effects between orography and other forcings tend to be largest in the Pacific-North American sector, which is beyond the scope of this paper, in agreement with Held et al (2002). On the other hand, Iles et al (2019) suggest that increasing the resolution of the orography and coastlines in climate simulations have limited benefits for temperature extremes over Europe, except in reducing hot biases over mountainous regions.…”
Section: Nonlinear Interactionssupporting
confidence: 72%
“…Changes in land cover can only slightly influence temperature by an additional cooling of 0.66 • C in MAM and a warming of 0.85 • C in JJA, both statistically significant (Table 3). Similarly, Jahn et al (2005) found that the LGM-like vegetation cover produces colder temperatures (ca. −0.6 • C globally), especially in areas with the greatest decrease in tree cover.…”
Section: Influence Of External Forcing and Land Cover On Climatementioning
confidence: 82%
“…One possible explanation for the disagreement is the coarse spatial resolution of the GCMs; at the continental scale, mountains, ice sheets, and water bodies have an important influence on regional circulation and climate that may not be represented appropriately at a typical GCM grid spacing of ca. 100 km (Rauscher et al, 2010;Gómez-Navarro et al, 2011Di Luca et al, 2012;Prein et al, 2013;Demory et al, 2020;Iles et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, by comparing the ensemble mean of projected change by the regional climate model, with 25km grid spacing in Southeast Asia (Supari et al, 2020), their results showed decreasing the PRCPTOT in northern Thailand, but the PRCTOT was generally located in eastern Thailand, with substantial decreasing patterns, while the rising pattern was in northern Thailand in this study. In general, increasing resolution may better capture small-scale processes and features (downscaling effect), but increased GCM resolution may also improve the representation of large-scale atmospheric circulation (upscaling effect) (Iles et al, 2020). Particularly, precipitation extremes are sensitive to resolution over complex orography.…”
Section: Resultsmentioning
confidence: 99%